ICU patients receiving remifentanil do not experience reduced duration of mechanical ventilation: a systematic review of randomized controlled trials and network meta-analyses based on Bayesian theories - Lu, Fangjie; Qin, Sirun; Liu, Chang; Chen, Xunxun; Dai, Zhaoqiu; Li, Cong (Frontiers in Medicine, 2024)
Background The purpose of this network meta-analysis (NMA) was to evaluate the efficacy of intravenous opioid μ-receptor analgesics in shortening the duration of mechanical ventilation (MV) in ICU patients. Methods Randomized controlled trials comparing the efficacy of remifentanil, sufentanil, morphine, and fentanyl on the duration of MV in ICU patients were searched in Embase, Cochrane, Pubmed, and Web of Science electronic databases. The primary outcome was MV duration. The Bayesian random-effects framework was used to evaluate relative efficacy. Results In total 20 studies were included in this NMA involving 3,442 patients. Remifentanil was not associated with a reduction in the duration of MV compared with fentanyl (mean difference (MD) -0.16; 95% credible interval (CrI): −4.75 5.63) and morphine (MD 3.84; 95% CrI: −0.29 10.68). The secondary outcomes showed that, compared with remifentanil, sufentanil can prolong the duration of extubation. No regimen significantly shortened the ICU length of stay and improved the ICU mortality, efficacy, safety, and drug-related adverse events. Conclusion Among these analgesics, remifentanil did not appear to be associated with a reduction in MV duration. Clinicians should carefully titrate the analgesia of MV patients to prevent a potentially prolonged duration of MV due to excessive or inadequate analgesic therapy. Systematic Review Registration https://www.crd.york.ac.uk/prospero/, CRD42021232604.